Distribution and development of molecularly distinct perineuronal nets in visual thalamus. Issue 5 (26th November 2018) - Sabbagh, Ubadah; Monavarfeshani, Aboozar; Su, Kaiwen; Zabet‐Moghadam, Masoud; Cole, James; Carnival, Eric; Su, Jianmin; Mirzaei, Mehdi; Gupta, Vivek; Salekdeh, Ghasem Hosseini; Fox, Michael A.
Abstract: Visual information is detected by the retina and transmitted into the brain by retinal ganglion cells. In rodents, the visual thalamus is a major recipient of retinal ganglion cells axons and is divided into three functionally distinct nuclei: the dorsal lateral geniculate nucleus (dLGN), ventral LGN (vLGN), and intergeniculate leaflet. Despite being densely innervated by retinal input, each nucleus in rodent visual thalamus possesses diverse molecular profiles which underpin their unique circuitry and cytoarchitecture. Here, we combined large‐scale unbiased proteomic and transcriptomic analyses to elucidate the molecular expression profiles of the developing mouse dLGN and vLGN. We identified several extracellular matrix proteins as differentially expressed in these regions, particularly constituent molecules of perineuronal nets (PNNs). Remarkably, we discovered at least two types of molecularly distinct Aggrecan‐rich PNN populations in vLGN, exhibiting non‐overlapping spatial, temporal, and cell‐type specific expression patterns. The mechanisms responsible for the formation of these two populations of PNNs also differ as the formation of Cat315 + PNNs (but not WFA + PNNs) required input from the retina. This study is first to suggest that cell type‐ and molecularly specific supramolecular assemblies of extracellular matrix may play important roles in the circuitry associated with the subcortical visual system and in the processing of visual information. Open science badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Cover Image for this issue: doi:10.1111/jnc.14203 . Abstract : The rodent dorsal and ventral lateral geniculate nuclei (dLGN and vLGN, respectively) both receive dense retinal input, yet exhibit unique circuitry and cytoarchitecture. Through combining proteomic and transcriptomic analyses, we discovered the presence of at least two types of molecularly distinct Aggrecan‐rich perineuronal nets (PNNs) in vLGN, each exhibiting non‐overlapping spatial, temporal, and cell‐type specific expression patterns. Further, by genetically removing retinal input, we showed activity‐dependent regulation of one type of PNN and not the other. Cover Image for this issue: doi:10.1111/jnc.14203 . Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/